Characterization of the disease-causing mechanism of KIF3B mutations from ciliopathy patients - Adams, Jessica M.; Sawe, Caleb; Rogers, Skye; Reid, Jordyn; Dasari, Ronith; Engelke, Martin F. (Frontiers in Molecular Biosciences, 2024)
The heterodimeric kinesin-2 motor (KIF3A/KIF3B with accessory protein KAP3) drives intraflagellar transport, essential for ciliogenesis and ciliary function. Three point mutations in the KIF3B subunit have recently been linked to disease in humans (E250Q and L523P) and Bengal cats (A334T) (Cogné et al., 2020). Patients display retinal atrophy and, in some cases, other ciliopathy phenotypes. However, the molecular mechanism leading to disease is currently unknown. Here, we used Kif3a -/-;Kif3b -/- (knockout) 3T3 cells, which cannot make cilia, to characterize these mutations. While reexpression of KIF3B(E250Q) and KIF3B(L523P) did not rescue ciliogenesis, reexpression of wildtype or KIF3B(A334T), restored ciliogenesis to wildtype levels. Fluorescent tagging revealed that the E250Q mutant decorated microtubules and thus is a rigor mutation. The L523P mutation, in the alpha-helical stalk domain, surprisingly did not affect formation of the KIF3A/KIF3B/KAP3 complex but instead impaired motility along microtubules. Lastly, expression of the A334T motor was reduced in comparison to all other motors, and this motor displayed an impaired ability to disperse the Golgi complex when artificially linked to this high-load cargo. In summary, this work uses cell-based assays to elucidate the molecular effects of disease-causing mutations in the KIF3B subunit on the kinesin-2 holoenzyme.